Automated data acquisition system for measurement resistivity using Van Der Pauw technique - Azri, Maaspaliza (2001)
This paper presented an automated data acquisition system for resistivity measurement by Van Der Pauw method (1). The system designed to measure the resistivity of superconductor at room temperature and low temperature. For low cost efficient measuring tool we integrated equipment standard such as I/O cards, sensors, constant current source and digital multimeter. This automated data acquisition system was written in Turbo Pascal.